Faktor Faktor yang Mempengaruhi Terjadinya Shivering pada Pasien Pasca Spinal Anestesi - Christanto, Dwi; Nani, Desiyani; Kaamaludin, Ridlwan (Journal of Telenursing (JOTING), 2023)
This study aims to determine the factors that influence the incidence of shivering in patients after spinal anesthesia. The method used was a systematic review of the incidence of shivering after spinal anesthesia. The results of this study show that spinal anesthesia causes shivering, which is influenced by the height of the spinal block, age, gender, length of operation, and body mass index (BMI). In conclusion, there is a relationship between age, gender, duration of surgery, body mass index (BMI), and the incidence of shivering in post-spinal anesthesia patients. All of these factors are related to each other. Keywords: Shivering, Spinal Anesthesia